2014
DOI: 10.1039/c4ra01555j
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric anion sensor based on receptor having indole- and thiourea-binding sites

Abstract: A new colorimetric sensor having nitro-substituted indole and bisthiocarbonohydrazone units for selective fluoride and acetate ions has been designed and synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…56 Recognition of anions also follows through electrostatic interactions 57 and coordination through metal ions, 58 etc. Hydrogen bonding involving NH and OH functional group 59,60 provides ample stabilization in the anion recognition and complex formation. It was found that the phenolic OH ionized and formed a strong complex in many receptor/anion complexes; however, the amide NH group mostly stabilized the complex via strong H-bond formation and was less susceptible to deprotonation compared to phenolic OH group present in the receptor.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…56 Recognition of anions also follows through electrostatic interactions 57 and coordination through metal ions, 58 etc. Hydrogen bonding involving NH and OH functional group 59,60 provides ample stabilization in the anion recognition and complex formation. It was found that the phenolic OH ionized and formed a strong complex in many receptor/anion complexes; however, the amide NH group mostly stabilized the complex via strong H-bond formation and was less susceptible to deprotonation compared to phenolic OH group present in the receptor.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Three 1D and 2D cobalt complexes were obtained. Solutions of complex 2 in DMF showed obvious color variation and fluorescence enhancement induced by the presence of acetate [20][21][22]. The thermal and gas adsorption properties of complexes 1 and 3 were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, anthracene, 10,11 anthraquinone, 12,13 calixpyrrole, 14,15 dipyrrolylquinoxaline, 16 and other chromophore molecules have been used as chromogenic units, displaying various colors and/or uorescence. In addition, uoride-binding motifs such as urea, 17,18 thiourea, 19,20 hydrazide, 21,22 indole, 23,24 and imidazole 23,25 groups have been adopted for selective recognition of uoride. The receptor groups mostly recognize uoride by Hbonding or deprotonation of the -NH moiety.…”
Section: Introductionmentioning
confidence: 99%